Nursing of integrated Traditional Chinese and Western medicine for a bed-ridden elderly patient with malignant tumor of cervical spine combined with incontinence-associated dermatitis (1例颈椎恶性肿瘤老年卧床患者并发失禁相关性皮炎的中西医结合护理) - DU Na (杜娜); WANG Jing (王静) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the experience of nursing of integrated Traditional Chinese and Western medicine for a bed-ridden elderly patient with malignant tumor of cervical spine combined with incontinence-associated dermatitis (IAD). Based on the dynamic evaluation and risk assessment, a systematic and integrated nursing plan was carried out, in which structured and targeted skin care, Traditional Chinese Medicine moxibustion and Chinese herbal tea were used jointly. The aim of integrated nursing is to regulate and balance the yin and yang of the whole body, and improve the recovery of the patient. (本文总结1例颈椎恶性肿瘤老年卧床患者并发失禁相关性皮炎(IAD)的中西医结合护理经验。通过开展动态评估, 运用整体护理理念, 将结构化皮肤护理方案与中医护理艾灸技术及中药代茶饮相结合, 局部皮肤进行对症处理, 整体调整患者身体脏腑阴阳, 全方位促进患者康复。)